The deep student: A thematic analysis of counsellor educators' perceptions and experiences. Issue 2 (23rd December 2021) - Tangen, Jodi L.; Fickling, Melissa J.; Cashwell, Craig S.
Abstract: What does it mean when we say a person is "deep" or has a lot of "depth?" We asked counsellor educators to describe the concept of personal depth, how it manifests in counsellors' work, and whether or not it could be trained. Twenty counsellor educators responded, and we analysed their responses using thematic analysis. We unearthed seven major themes of the construct: nondual consciousness, emotions, cognitions, interpersonal attributes, self‐awareness, attitude and life experiences. Participants also provided suggestions for training students to cultivate personal depth. Finally, we introduce a depth wheel to conceptualise our results and provide implications for counselling and training.